(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
This article deals with the issues based on the application of Problem-Based Learning (PBL) as a transformative educational approach for developing students’ creative skills. Creativity, defined as the ability to generate novel and practical solutions to problems, is a critical skill in today’s dynamic and interdisciplinary world. The study examines the theoretical underpinnings of PBL, focusing on its roots in experiential learning and its emphasis on active problem-solving. The integration of innovative strategies, such as Gamification, project-based learning, and interdisciplinary collaboration, within PBL frameworks is analyzed to demonstrate their effectiveness in fostering creativity